Negative electrode and secondary battery including the same
By using side-by-side combined carbon nanotube structure and the second negative electrode active material layer of SiOx material in lithium secondary batteries, the conductive network fracture and adhesive migration problems caused by changes in the volume of silicon-based active material are solved, and the battery is improved Input/output characteristics and life characteristics.
Patent Information
- Application Number
- CN202411269213.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-22
- Filing Date
- 2021-04-21
- Publication Date
- 2024-12-20
AI Technical Summary
In existing lithium secondary batteries, the volume expansion and contraction of silicon-based active materials lead to single-wall carbon nanotube fracture, the conductive network is blocked or reduced, resulting in deterioration of battery life characteristics, and low solid content carbon nanotube dispersions lead to Adhesives and conductive agents migrate, reducing the adhesion and conductivity of the negative electrode.
Using a second negative active material layer of carbon nanotube structure including 2 to 5,000 single-wall carbon nanotubes side by side, combined with SiOx (0≤x<2) material, the conductive network is kept intact by rolling pressure and minimized bonding The agent is migrated to enhance the adhesion and conductivity of the negative electrode.
Effectively maintain the integrity of the conductive network, improve the input/output characteristics and life characteristics of the battery, reduce adhesive migration, enhance the adhesion between the negative electrode and the current collector, and extend the battery life.
Smart Images

Figure CN119170740A_ABST
Abstract
Description
[0001] This application is a divisional application of a Chinese patent application with an application date of April 21, 2021, an application number of "202180006436.X", and an invention name of "Negative electrode and secondary battery including the negative electrode". Technical Field
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims the benefit of Korean Patent Application No. 10-2020-0048940, filed on April 22, 2020, the disclosure of which is incorporated herein by reference. Technical Field
[0005] The present invention relates to a negative electrode and a secondary battery comprising the negative electrode, wherein the negative electrode comprises a negative electrode current collector, a first negative electrode active material layer disposed on the negative electrode current collector, and a second negative electrode active material layer disposed on the first negative electrode active material layer, wherein the second negative electrode active material layer comprises a second negative electrode active material and a second conductive agent, wherein the second negative electrode active material comprises a silicon-based active material, and the silicon-based active material comprises SiO x (0≤x<2), the second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined side by side, and the carbon nanotube structure is included in the second negative active material layer in an amount of 0.01 wt % to 1.0 wt %. Background Art
[0006] With the recent technological development and increase in demand for mobile devices, the demand for batteries as energy sources has increased significantly, and accordingly various studies have been conducted on batteries that can meet various demands. In particular, lithium secondary batteries with excellent life and cycle characteristics and high energy density as power sources for such devices have been actively studied.
[0007] A lithium secondary battery refers to a battery that includes a non-aqueous electrolyte containing lithium ions in an electrode assembly, the electrode assembly comprising: a positive electrode containing a positive electrode active material capable of inserting / deinserting lithium ions, a negative electrode containing a negative electrode active material capable of inserting / deinserting lithium ions, and a microporous separator disposed between the positive electrode and the negative electrode.
[0008] Since the conductivity of the negative electrode cannot be ensured only by the negative electrode active material, the resistance of the battery may be too high, and therefore, the negative electrode generally includes a conductive agent in addition. Generally, a point-type conductive agent such as carbon black is mainly used, and a linear conductive agent such as carbon nanotubes and carbon nanofibers is also used to increase the battery capacity by further improving the conductivity.
[0009] Single-walled carbon nanotubes are one of the linear conductive agents and improve the conductivity in the negative electrode active material layer due to their elongated shape. Therefore, generally, after preparing a negative electrode slurry using a dispersion liquid in which single-walled carbon nanotubes are completely dispersed, the negative electrode active material layer is prepared by using the negative electrode slurry.
[0010] However, when the battery is repeatedly charged and discharged, the single-walled carbon nanotubes break as the volume expansion and contraction of the negative electrode active material are repeated, and therefore, it may be difficult to maintain the conductive network in the negative electrode active material layer. In particular, in the case of using silicon-based active materials as negative electrode active materials to increase the battery capacity, the breakage of the single-walled carbon nanotubes is more serious because the volume of the silicon-based active materials is excessively expanded due to the charging and discharging of the battery. Therefore, the conductive network is blocked or reduced, which deteriorates the life characteristics of the battery. In addition, since the single-walled carbon nanotubes surround the surface of the silicon-based active material, it may not be able to smoothly play the role of electrically connecting adjacent negative electrode active materials to each other.
[0011] In the case of using carbon nanotubes as a conductive agent, in order to make the carbon nanotubes uniformly arranged in the negative electrode active material layer, a carbon nanotube dispersion with a low solid content must be used. However, if a carbon nanotube dispersion with a low solid content is used, there is a problem in that the binder and the conductive agent having a relatively lower density than the negative electrode active material are easily moved to the upper part of the negative electrode active material layer (away from the current collector and close to the surface) during the drying of the negative electrode, and the negative electrode adhesion and conductivity are significantly reduced due to this migration phenomenon.
[0012] Therefore, the present invention introduces a negative electrode in which a conductive network can be connected even if the volume of the negative electrode active material varies greatly, and problems caused by the migration phenomenon of the binder can be minimized. Summary of the invention
[0013] Technical issues
[0014] One aspect of the present invention provides a negative electrode that can improve input / output characteristics and lifespan characteristics by minimizing problems caused by a migration phenomenon of a binder while maintaining a smooth conductive network.
[0015] Another aspect of the present invention provides a secondary battery including the negative electrode.
[0016] Technical Solution
[0017] According to one aspect of the present invention, there is provided a negative electrode, comprising a negative electrode current collector, a first negative electrode active material layer disposed on the negative electrode current collector, and a second negative electrode active material layer disposed on the first negative electrode active material layer, wherein the second negative electrode active material layer comprises a second negative electrode active material and a second conductive agent, wherein the second negative electrode active material comprises a silicon-based active material, and the silicon-based active material comprises SiO x (0≤x<2), the second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined side by side, and the carbon nanotube structure is included in the second negative active material layer in an amount of 0.01 wt % to 1.0 wt %.
[0018] According to another aspect of the present invention, a secondary battery including the negative electrode is provided.
[0019] Beneficial Effects
[0020] Since the second negative electrode active material layer of the negative electrode according to the present invention includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined side by side in the form of a long rope, even if SiO2 of the second negative electrode active material layer is formed during roll pressing, x The volume change of (0≤x<2) is large, and the carbon nanotube structure can also firmly hold the second negative electrode active material particles together while connecting the second negative electrode active material particles, and SiO x (0≤x<2) can suppress damage (e.g., cracks). In addition, since the negative electrode has a first negative electrode active material layer and a second negative electrode active material layer sequentially arranged according to their respective slurries, the migration phenomenon of the above-mentioned binder and conductive agent can be minimized. In addition, since the second negative electrode active material layer includes a carbon nanotube structure, the adhesion between the first negative electrode active material layer and the second negative electrode active material layer can be strengthened. Therefore, the input / output characteristics and life characteristics of the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Analytical diagram of the binder distribution in the negative electrode of Comparative Example 1 and the negative electrode of Example 1;
[0022] Figure 2 A scanning electron microscope (SEM) image of the second negative electrode active material layer of the negative electrode of Example 1;
[0023] Figure 3 is a SEM image of the second negative electrode active material layer of the negative electrode of Example 2;
[0024] Figure 4 A SEM image of the second negative electrode active material layer of the negative electrode of Comparative Example 3;
[0025] Figure 5 is a SEM image of the second negative electrode active material layer of the negative electrode of Example 1; and
[0026] Figure 6 3 is a SEM image of the second negative electrode active material layer of the negative electrode of Comparative Example 2. DETAILED DESCRIPTION
[0027] It will be understood that the words or terms used in this specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it will be further understood that, based on the principle that the inventor can appropriately define the meanings of words or terms in order to best explain the present invention, the words or terms should be interpreted as having a meaning consistent with the meaning in the context of the relevant art and the technical concept of the present invention.
[0028] The terms used herein are for the purpose of describing specific example embodiments only and are not intended to limit the present invention. In the present specification, terms in the singular form may include plural forms unless otherwise specified.
[0029] It will be further understood that the terms "comprises," "includes," or "has," when used in this specification, specify the presence of claimed features, values, steps, elements, or combinations thereof, but do not preclude the presence or addition of one or more other features, values, steps, elements, or combinations thereof.
[0030] In the present specification, unless otherwise specifically stated, the expression "%" means % by weight.
[0031] In this specification, the expression "specific surface area" is measured by the Brunauer-Emmett-Teller (BET) method, wherein, specifically, the specific surface area can be calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77K) using BELSORP-mini II of Bel Japan Co., Ltd.
[0032] The expression "average particle size (D 50 )” can be defined as the particle size at which the cumulative volume in the particle size distribution curve is 50%. For example, the average particle size (D 50 ) can be measured by using a laser diffraction method. The laser diffraction method can generally measure particle sizes from submicron level to several millimeters, and can obtain results with high reproducibility and high resolution.
[0033] In the present invention, the expression "single-wall carbon nanotube unit" means a unit in the form of a single-wall tube composed of carbon atoms, and the expression "multi-wall carbon nanotube unit" means a unit in the form of a multi-wall tube composed of carbon atoms.
[0034] Hereinafter, the present invention will be described in detail.
[0035] <Negative electrode>
[0036] The negative electrode according to an embodiment of the present invention includes a negative electrode current collector, a first negative electrode active material layer disposed on the negative electrode current collector, and a second negative electrode active material layer disposed on the first negative electrode active material layer, wherein the second negative electrode active material layer includes a second negative electrode active material and a second conductive agent, wherein the second negative electrode active material includes a silicon-based active material, and the silicon-based active material includes SiO x (0≤x<2), the second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined side by side, and the carbon nanotube structure is included in the second negative active material layer in an amount of 0.01 wt % to 1.0 wt %.
[0037] The negative electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, and the like can be used as the negative electrode current collector. Specifically, transition metals such as copper and nickel that absorb carbon well can be used as the negative electrode current collector.
[0038] The negative electrode may include a negative electrode active material layer. The negative electrode active material layer may be disposed on one surface or both surfaces of the negative electrode current collector.
[0039] The negative electrode active material layer may include a first negative electrode active material layer and a second negative electrode active material layer. The first negative electrode active material layer may be disposed on the negative electrode current collector, and specifically may be in contact with the negative electrode current collector. The second negative electrode active material layer may be disposed on the first negative electrode active material layer, and the first negative electrode active material layer may be disposed between the second negative electrode active material layer and the negative electrode current collector.
[0040] Generally, when using carbon nanotubes as a conductive agent, a carbon nanotube dispersion with a low solid content can be used to uniformly arrange the carbon nanotubes in the negative electrode active material layer. However, when using a carbon nanotube dispersion with a low solid content, there is a problem in that the binder and the conductive agent having a relatively lower density than the negative electrode active material are easily moved to the upper part of the negative electrode active material layer (away from the collector and close to the surface direction) during the drying of the negative electrode slurry, and the negative electrode adhesion and conductivity are significantly reduced due to this phenomenon (migration). In contrast, since the negative electrode of the present invention has a first negative electrode active material layer and a second negative electrode active material layer arranged in sequence according to their respective slurries, the migration phenomenon of the above-mentioned binder and conductive agent can be minimized. Therefore, the input / output characteristics and life characteristics of the battery can be improved.
[0041] (1) First negative electrode active material layer
[0042] The first negative active material layer may include a first negative active material.
[0043] The first negative electrode active material may be a negative electrode active material commonly used in the art, and its type is not particularly limited.
[0044] Specifically, the first negative electrode active material may include at least one of a carbon-based active material and a silicon-based active material. At least one selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fiber, and graphitized mesophase carbon microbeads may be used as the carbon-based active material. In particular, when artificial graphite is used, the rate performance may be improved. x As the silicon-based active material, at least one of the group consisting of (0≤x<2), Si-C composites, and Si-Y alloys (wherein Y is an element selected from the group consisting of alkali metals, alkaline earth metals, transition metals, Group 13 elements, Group 14 elements, rare earth elements, and combinations thereof) is used, especially when SiO x When (0≤x<2), a high battery capacity can be obtained. More specifically, the first negative electrode active material can be a carbon-based active material.
[0045] The first negative electrode active material may be included in the first negative electrode active material layer in an amount of 70 wt % to 99.5 wt %, for example, 80 wt % to 99 wt %. When the amount of the first negative electrode active material satisfies the above range, the energy density of the negative electrode may be increased, the negative electrode adhesion may be increased, and the conductivity of the negative electrode may be increased.
[0046] The first negative active material layer may further include a first conductive agent.
[0047] The first conductive agent may include at least one selected from the group consisting of a carbon nanotube structure, a multi-walled carbon nanotube unit, graphene, and carbon black. The carbon nanotube structure will be described in detail later.
[0048] The first conductive agent may be included in the first negative electrode active material layer in an amount of 0.01 wt % to 2.0 wt %, particularly 0.01 wt % to 1.5 wt %, and more particularly 0.05 wt % to 1.0 wt %. When the amount of the first conductive agent satisfies the above range, even with a small amount of the first conductive agent, the adhesion and conductivity of the negative electrode can be significantly improved, and a battery having excellent input / output characteristics and life characteristics can be realized.
[0049] The thickness of the first negative electrode active material layer may be 1 μm to 100 μm, particularly 5 μm to 90 μm, and more particularly 10 μm to 80 μm. When the thickness of the first negative electrode active material layer satisfies the above range, the migration phenomenon of the above-mentioned binder and conductive agent can be minimized. Therefore, the adhesion and conductivity of the negative electrode can be significantly improved, and the input / output characteristics and life characteristics of the battery can be improved.
[0050] (2) Second negative electrode active material layer
[0051] The second negative active material layer may include a second negative active material and a second conductive agent.
[0052] The second negative electrode active material may include a silicon-based active material.
[0053] Silicon-based active materials may include SiO x (0≤x<2).SiO x (0≤x<2) may specifically be SiO. Since the second negative electrode active material includes SiO x (0≤x<2), so the capacity of the battery can be improved. In particular, since the second negative electrode active material layer rather than the first negative electrode active material layer includes SiO x (0≤x<2), thus the durability of the negative electrode can be improved and the electrolyte impregnation can be improved. More specifically, at the interface between the negative electrode current collector and the negative electrode active material layer, which has the weakest binding force in the negative electrode, there is a problem that the negative electrode active material is easily peeled off from the negative electrode due to the shrinkage and expansion of the negative electrode active material during the charge and discharge of the battery. x When (0≤x<2) is located near the negative electrode current collector, the above-mentioned peeling phenomenon is aggravated. Therefore, the durability of the negative electrode is reduced, and the capacity and life characteristics of the battery are deteriorated.
[0054] During the rolling process of the negative electrode preparation process, the density near the negative electrode surface becomes too high, and thus the electrolyte impregnation is reduced. x(0≤x<2) is located near the negative electrode surface, due to the SiO x The volume expansion of (0≤x<2) leads to a decrease in the density of the negative electrode to a suitable level and can improve the electrolyte impregnation.
[0055] The silicon-based active material may further include a x (0≤x<2). The carbon coating can be provided on SiO x (0≤x<2). Carbon coating increases the SiO x (0≤x<2) conductivity and inhibits SiO x The effect of excessive volume expansion of (0≤x<2).
[0056] The carbon coating may include at least one of amorphous carbon and crystalline carbon.
[0057] The crystalline carbon can further improve the conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fullerene, carbon nanotube, and graphene.
[0058] Amorphous carbon can suppress expansion of natural graphite by appropriately maintaining the strength of the coating.Amorphous carbon may be a carbide of at least one selected from the group consisting of tar, pitch, and other organic materials, or may be a carbon-based material formed by using hydrocarbons as a chemical vapor deposition source.
[0059] The carbide of other organic materials may be a carbide of sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose or ketohexose, and a carbide of an organic material selected from a combination thereof.
[0060] Hydrocarbon can be substituted or unsubstituted aliphatic hydrocarbon or alicyclic hydrocarbon or substituted or unsubstituted aromatic hydrocarbon.Substituted or unsubstituted aliphatic hydrocarbon or alicyclic hydrocarbon can comprise pyrethrin, ethynyl, ethylene, acetylene, propane, butane, butylene, pentane, isobutane or hexane.Substituted or unsubstituted aromatic hydrocarbon can comprise benzene, toluene, xylene, vinylbenzene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene or phenanthrene.
[0061] The average particle size of silicon-based active materials (D 50 ) can be 0.1 μm to 20 μm, for example, 1 μm to 10 μm. When the average particle size satisfies the above range, SiO x The side reaction between (0≤x<2) and the electrolyte can be controlled by x (0≤x<2) lithium silicate forming reaction to prevent the decrease of initial efficiency and maximize the initial capacity of the battery.
[0062] The second negative electrode active material may further include a carbon-based active material. The carbon-based active material may include at least one selected from the group consisting of artificial graphite, natural graphite, and graphitized mesophase carbon microbeads. Specifically, the carbon-based active material may be artificial graphite in terms of the fact that artificial graphite can effectively control the volume expansion of the negative electrode while maintaining an electrical network with the carbon nanotube structure described later, but the carbon-based active material is not limited thereto.
[0063] The weight ratio of the silicon-based active material to the carbon-based active material may be in the range of 0.5:99.5 to 20:80, for example, 1:99 to 10:90. When the above range is met, the capacity of the battery can be increased while suppressing excessive volume expansion of the second negative electrode active material.
[0064] The second negative electrode active material may be included in the second negative electrode active material layer in an amount of 90 wt %, for example, 95 wt % to 99 wt %. When the above range is met, the energy density of the negative electrode can be highly maintained, and the conductivity and adhesion of the negative electrode can be improved.
[0065] The second conductive agent may further include a carbon nanotube structure.
[0066] The carbon nanotube structure may include a plurality of single-walled carbon nanotube units. Specifically, the carbon nanotube structure may be a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined side by side with each other. More specifically, in view of the conductive network and durability of the second negative electrode active material layer, the carbon nanotube structure may be a carbon nanotube structure in which 2 to 4,500 single-walled carbon nanotube units, preferably 2 to 4,000 single-walled carbon nanotube units, and more preferably 2 to 200 single-walled carbon nanotube units are combined with each other. In view of the improvement of the dispersibility of the carbon nanotube structure and the durability of the negative electrode, the carbon nanotube structure may be a carbon nanotube structure in which 2 to 50 single-walled carbon nanotube units are arranged side by side and combined together.
[0067] In the carbon nanotube structure, the single-walled carbon nanotube units can be arranged side by side and combined (a cylindrical structure in the form of a bundle, in which the long axes of each unit are combined parallel to each other to have flexibility) to form a carbon nanotube structure. The carbon nanotube structure can be interconnected to form a network structure in the second negative electrode active material layer.
[0068] Conventional electrodes including carbon nanotubes are generally prepared by dispersing bundle type or entangled type carbon nanotubes (in a form in which single-walled carbon nanotube units or multi-walled carbon nanotube units are attached or entangled with each other) in a dispersion medium to prepare a conductive agent dispersion, and then using the conductive agent dispersion. In this case, the carbon nanotubes are completely dispersed in the conventional conductive agent dispersion to exist as a conductive agent dispersion in which carbon nanotube units in a single chain form are dispersed. In this case, in the conventional conductive agent dispersion, the carbon nanotube units are easily cut by an excessive dispersion process, so that the length of the carbon nanotube units is shorter than the initial length. In addition, the carbon nanotube units are also easily cut in the rolling process of the negative electrode, and another limitation is that the carbon nanotube units (especially the single-walled carbon nanotube units) are cut due to excessive volume changes of the silicon-based active material during the operation of the battery. Therefore, the conductivity of the negative electrode is reduced, thereby deteriorating the life characteristics of the battery. In addition, for the multi-walled carbon nanotube unit, due to the mechanism of node growth (not a smooth linear shape, but the node exists due to defects generated during the growth process), the structural defects are high. Therefore, during the dispersion process, the multi-walled carbon nanotube unit is more easily cut, and the cut multi-walled carbon nanotube unit is likely to agglomerate with each other via π-π stacking of the carbon of the unit. Therefore, it is difficult for the multi-walled carbon nanotube unit to be more uniformly dispersed and present in the negative electrode slurry.
[0069] Alternatively, for the carbon nanotube structure contained in the second negative electrode active material layer of the present invention, since the carbon nanotube structure is a rope-shaped structure in which 2 to 5,000 single-walled carbon nanotube units that maintain a relatively high crystallinity and are relatively free of structural defects are arranged side by side and bonded together, even if the volume of the second negative electrode active material changes, the single-walled carbon nanotube units are not cut, and their lengths can be smoothly maintained, and therefore, the conductivity of the negative electrode can be maintained even during the continuous charge / discharge process of the battery. In addition, since the high conductivity of the single-walled carbon nanotube units with high crystallinity leads to increased conductivity of the negative electrode, the resistance of the negative electrode can be reduced and the input / output characteristics and life characteristics of the battery can be significantly improved. In addition, since the carbon nanotube structure can be directly interconnected under pressure during rolling to have a network structure in the second negative electrode active material layer, damage to the second negative electrode active material (e.g., a fracture phenomenon such as a crack) can be suppressed. In addition, even if a crack is generated in the second negative electrode active material, since the carbon nanotube structure can connect the second negative electrode active material while crossing the crack, the conductive network can be maintained. In addition, since the carbon nanotube structure is not easily broken and can maintain its long shape, the conductive network can be strengthened throughout the second negative electrode active material layer. In addition, by suppressing the peeling of the second negative electrode active material, the negative electrode adhesion can be significantly improved.
[0070] In addition, since the carbon nanotube structure is included in the second negative electrode active material layer, the adhesion between the first negative electrode active material layer and the second negative electrode active material layer can be significantly improved. Due to the form of a long rope formed by the lateral bonding of the single-walled carbon nanotube units in the carbon nanotube structure, the second negative electrode active material particles can be well connected to each other via van der Waals force, and the negative electrode can be firmly configured. In addition, since the surface of the carbon nanotube structure and the carbon-based active material of the first negative electrode active material layer can be more closely bonded by π-π bonding (stacking) occurring between the same type of carbon, the adhesion between the first negative electrode active material layer and the second negative electrode active material layer can be further enhanced.
[0071] In the carbon nanotube structure, the average diameter of the single-walled carbon nanotube unit can be 0.5nm to 10nm, for example, 1nm to 9nm. When the average diameter is met, even if a very small amount of conductive agent is used, it has the effect of maximizing the conductivity of the negative electrode. When the prepared negative electrode is observed by a transmission electron microscope (TEM), the average diameter corresponds to the average value of the diameters of the first 100 single-walled carbon nanotube units and the last 100 single-walled carbon nanotube units having a large diameter.
[0072] In the carbon nanotube structure, the average length of the single-walled carbon nanotube unit may be 1 μm to 100 μm, for example, 5 μm to 50 μm. When the average length is satisfied, since a long conductive path for conductive connection between the second negative electrode active material particles can be formed and a unique network structure can be formed, even with a very small amount of conductive agent, it has the effect of maximizing the conductivity of the negative electrode. When the prepared negative electrode is observed by TEM, the average length corresponds to the average value of the first 100 single-walled carbon nanotube units having a long length and.
[0073] The specific surface area (BET) of a single-walled carbon nanotube unit can be 500 m 2 / g to 1,000m 2 / g, for example 600m 2 / g to 800m 2 / g. When the above range is met, the conductive path in the negative electrode can be smoothly ensured due to the large specific surface area, so even if a very small amount of conductive agent is used, it has the effect of maximizing the conductivity of the negative electrode. The specific surface area of the single-walled carbon nanotube unit can be calculated from the nitrogen adsorption at liquid nitrogen temperature (77K) using BELSORP-mini II of BEL Japan Co., Ltd.
[0074] The average diameter of the carbon nanotube structure may be 2 nm to 200 nm, particularly 5 nm to 200 nm, and more particularly 5 nm to 50 nm. When the above range is met, excellent conductivity can be achieved due to the effective formation of a conductive network and the connection between the second negative electrode active material particles. When the prepared negative electrode is observed by a scanning electron microscope (SEM), the average diameter corresponds to the average of the diameters of the first 100 carbon nanotube structures and the last 100 carbon nanotube structures having a large diameter.
[0075] The average length of the carbon nanotube structure can be 1 μm to 500 μm, particularly 1 μm to 100 μm, and more particularly 2 μm to 50 μm. When the above range is met, excellent conductivity can be achieved due to the effective formation of a conductive network and the connection between the second negative electrode active material particles. When the prepared negative electrode is observed by SEM, the average length corresponds to the average of the lengths of the first 100 carbon nanotube structures and the last 100 carbon nanotube structures having a long length.
[0076] The carbon nanotube structure may be included in the second negative electrode active material layer in an amount of 0.01 wt % to 1.0 wt %, particularly 0.01 wt % to 0.5 wt %, and particularly 0.01 wt % to 0.2 wt %. When the above range is satisfied, since the conductive path of the second negative electrode active material layer can be ensured, the life characteristics of the battery can be improved while maintaining a low level of negative electrode resistance.
[0077] In the case where the bundle-type carbon nanotubes are completely dispersed during the preparation of the conductive agent dispersion (as a general dispersion method, dispersion is performed so that the single-chain carbon nanotube units are separated from each other as much as possible), the carbon nanotube structure is not formed, or, even if the carbon nanotube structure is formed unintentionally, the amount of the carbon nanotube structure formed is very small (for example, 0.0005 wt%). That is, the above content range may never be achieved by a general method. Since the carbon nanotube structure has a form in which 2 to 5,000 single-walled carbon nanotube units are arranged side by side and combined together, even if the volume of the second negative electrode active material changes, the single-walled carbon nanotube units are not cut off, and their lengths can be smoothly maintained. Therefore, the conductive network of the second negative electrode active material layer can be maintained, and due to the high conductivity of the carbon nanotube structure, the conductivity of the second negative electrode active material layer can be smoothly ensured. Therefore, even if the content of the carbon nanotube structure in the second negative electrode active material layer is low, the input / output characteristics and life characteristics of the battery can be excellent.
[0078] In some cases, the single-walled carbon nanotube units may be surface treated by oxidation or nitridation to improve affinity with the dispersant.
[0079] The second conductive agent may further include at least one selected from the group consisting of fullerene, carbon black, carbon nanotubes and graphene. In this case, since the one-dimensional linear conductive network can be transformed into a two-dimensional or higher-dimensional conductive network through the composite application of the above materials and the carbon nanotube structure, the conductivity of the second negative electrode active material layer can be improved, and the input / output characteristics and life characteristics of the battery can be improved.
[0080] The thickness of the second negative electrode active material layer may be 1 μm to 100 μm, particularly 5 μm to 90 μm, and more particularly 10 μm to 80 μm. When the thickness of the second negative electrode active material layer satisfies the above range, the migration phenomenon of the above-mentioned binder and conductive agent can be minimized. Therefore, the adhesion of the negative electrode (adhesion between the negative electrode active material layer and the collector), the adhesion between the first negative electrode active material layer and the second negative electrode active material layer, and the conductivity of the negative electrode can be significantly improved, and the input / output characteristics and life characteristics of the battery can be improved.
[0081] The thickness of the second negative electrode active material layer may be greater than or equal to the thickness of the first negative electrode active material layer. The ratio of the thickness of the first negative electrode active material layer to the thickness of the second negative electrode active material layer may be in the range of 10:90 to 50:50, particularly 20:80 to 50:50, and more particularly 25:75 to 50:50. In the case where the ratio does not satisfy the above range, the effect of suppressing the migration phenomenon of the above-mentioned binder and conductive agent is reduced, and the effect of increasing the diffusion resistance by increasing the porosity of the second negative electrode active material layer is reduced. Even when the thickness of the first negative electrode active material layer is outside the above range and is too thin, the effect of improving the negative electrode adhesion and the interface resistance becomes negligible due to the reduced effect of suppressing the migration phenomenon of the above-mentioned binder and conductive agent.
[0082] There is an interface between the first negative electrode active material layer and the second negative electrode active material layer. This can be confirmed by a cross section of the prepared negative electrode. In contrast, if the negative electrode active material layer is formed into a single layer structure (by using a single negative electrode slurry for only one coating) instead of a multilayer structure, no interface is observed.
[0083] The first negative electrode active material layer and the second negative electrode active material layer may each further include a binder, and the binder of the first negative electrode active material layer and the binder of the second negative electrode active material layer may be the same or may be different from each other. The binder is used to ensure the adhesion between the negative electrode active materials or the adhesion of the negative electrode active material to the collector, wherein the binder commonly used in the art can be used, and there is no particular restriction on its type. For example, the binder may include polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, carboxymethyl cellulose (carboxymethyl cellulose: CMC), styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, any one of them or a mixture of two or more thereof may be used.
[0084] The binder may be included in the first negative electrode active material (or the second negative electrode active material layer) in an amount of 10 wt % or less, for example, 0.1 wt % to 5 wt %. When the content of the binder satisfies the above range, when the amount of the binder satisfies the above range, excellent negative electrode adhesion can be achieved while minimizing the increase in negative electrode resistance.
[0085] Method for preparing negative electrode
[0086] Next, a method for producing the negative electrode of the present invention will be described.
[0087] The method for preparing the negative electrode of the present invention comprises the following steps: preparing a first negative electrode slurry and a second negative electrode slurry; forming a first negative electrode active material layer on a negative electrode current collector using the first negative electrode slurry; and forming a second negative electrode active material layer on the first negative electrode active material layer using the second negative electrode slurry, wherein the second negative electrode slurry comprises a second negative electrode active material and a second conductive agent, wherein the second negative electrode active material comprises a silicon-based active material, and the silicon-based active material comprises SiO x (0≤x<2), the second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined side by side, and the carbon nanotube structure is included in the second negative electrode active material layer in an amount of 0.01 wt % to 1.0 wt %. The first negative electrode active material layer, the second negative electrode active material layer, the second negative electrode active material, the second conductive agent, and the carbon nanotube structure are the same as those in the above-mentioned embodiment.
[0088] (1) Preparation of the first negative electrode slurry and the second negative electrode slurry
[0089] The method for preparing the first negative electrode slurry may be the same as the conventional method for preparing the negative electrode slurry. For example, after preparing a mixture including a first negative electrode active material (the same as the first negative electrode active material of the above embodiment), a first conductive agent (the same as the first conductive agent of the above embodiment) and a solvent (which may further include a binder), the mixture is stirred to prepare the first negative electrode slurry.
[0090] However, in the case where the first negative electrode slurry includes a carbon nanotube structure, a carbon nanotube structure dispersion described later may be prepared.
[0091] For example, the solvent may include: water; an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP); an alcohol such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol, or octanol; a glycol such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,5-pentanediol, or hexanediol. Diol; polyol, such as glycerol, trimethylolpropane, pentaerythritol, or sorbitol; glycol ether, such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, or tetraethylene glycol monobutyl ether; ketone, such as acetone, methyl ethyl ketone, methyl propyl ketone, or cyclopentanone; and ester, such as ethyl acetate, γ-butyl lactone, and ε-propiolactone, any one of them or a mixture of two or more thereof can be used, but the present invention is not limited thereto. The solvent may be the same as or different from the dispersion medium used for the conductive agent dispersion, and the solvent may preferably be water.
[0092] After preparing a mixture including the second negative electrode active material, the carbon nanotube structure dispersion, and a solvent, a second negative electrode slurry may be prepared by stirring the mixture.
[0093] The carbon nanotube structure dispersion can be prepared as follows.
[0094] The preparation of a carbon nanotube structure dispersion may include the following steps: preparing a mixed solution containing a dispersion medium, a dispersant and bundled single-walled carbon nanotubes (a combination or agglomeration of single-walled carbon nanotube units) (S1-1); and dispersing the bundled single-walled carbon nanotubes by applying a shear force to the mixed solution to form a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined side by side (S1-2).
[0095] In step S1-1, a mixed solution can be prepared by adding bundled single-walled carbon nanotubes and a dispersant to a dispersion medium. The bundled single-walled carbon nanotubes exist in the form of bundles in which the above-mentioned single-walled carbon nanotube units are bound together, wherein the bundled carbon nanotubes generally include 2 or more, substantially 500 or more, for example 5,000 or more single-walled carbon nanotube units.
[0096] The specific surface area of bundled single-walled carbon nanotubes can be 500m 2 / g to 1,200m 2 / g, for example 500m 2 / g to 1,000m2 When the above range is met, since the wide specific surface area can smoothly ensure the conductive path in the second negative electrode active material layer, even if a very small amount of conductive agent is used, it has the effect of maximizing the conductivity of the second negative electrode active material layer. In addition, in order to enhance the adhesion between the first negative electrode active material layer and the second negative electrode active material layer, the specific surface area is preferably 500m 2 / g to 800m 2 / g range.
[0097] The bundle-type single-walled carbon nanotubes may be included in the mixed solution in an amount of 0.1 wt % to 1.0 wt %, for example, 0.2 wt % to 0.5 wt %. When the above range is satisfied, since the bundle-type single-walled carbon nanotubes are dispersed at an appropriate level, a carbon nanotube structure may be formed at an appropriate level and dispersion stability may be improved.
[0098] For example, the dispersion medium may include: water; an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP); an alcohol such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol, or octanol; a glycol such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,5-pentanediol, or Hexanediol; polyols such as glycerol, trimethylolpropane, pentaerythritol, or sorbitol; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, or tetraethylene glycol monobutyl ether; ketones such as acetone, methyl ethyl ketone, methyl propyl ketone, or cyclopentanone; and esters such as ethyl acetate, γ-butyl lactone, and ε-propiolactone, any one of them or a mixture of two or more thereof may be used, but the present invention is not limited thereto. Specifically, the dispersion medium may be the same as or different from the solvent used to prepare the negative electrode slurry, and the dispersion medium may preferably be water.
[0099] The dispersant may include at least one selected from hydrogenated nitrile rubber, polyvinylidene fluoride, polystyrene, polyvinyl pyrrolidone, polyvinyl alcohol, pyrenebutyric acid, pyrenesulfonic acid, tannic acid, pyrenemethylamine, sodium lauryl sulfate, and carboxymethyl cellulose, and specifically may be carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, or hydrogenated nitrile rubber.
[0100] The weight ratio of the bundle-type carbon nanotubes to the dispersant in the carbon nanotube structure dispersion may be in the range of 1:0.1 to 1:10, for example, 1:1 to 1:10. When the above range is satisfied, since the bundle-type single-walled carbon nanotubes are dispersed at an appropriate level, the carbon nanotube structure may be formed at an appropriate level and the dispersion stability may be improved.
[0101] The solid content in the mixed solution may be in the range of 0.1 wt % to 20 wt %, for example, 1 wt % to 10 wt %. In the case where the above range is met, since the bundle-type single-walled carbon nanotubes are dispersed at an appropriate level, the carbon nanotube structure may be formed at an appropriate level and the dispersion stability may be improved. In addition, the second negative electrode slurry (slurry for preparing the second negative electrode active material layer) may have a viscosity and elasticity suitable for forming the second negative electrode active material layer, and also contributes to increasing the solid content of the second negative electrode active material layer.
[0102] In step S1-2, the process of dispersing the bundle-type carbon nanotubes in the mixed solution can be carried out by using a mixing device such as a homogenizer, a bead mill, a ball mill, a basket mill, a grinder, a universal stirrer, a transparent mixer, a pin crusher, a TK mixer, or an ultrasonic (sonification) device. Among them, the beads mill method is preferred because it can accurately control the diameter of the carbon nanotube structure, can achieve uniform distribution of the carbon nanotube structure, and can have advantages in terms of cost.
[0103] The bead milling method may be as follows: The mixed solution may be put into a container containing beads, and the container may be rotated to disperse the bundle-type single-walled carbon nanotubes.
[0104] In this case, the conditions for performing the bead milling method are as follows.
[0105] The average diameter of the beads may be 0.5 to 1.5 mm, for example 0.5 to 1.0 mm. When the average diameter satisfies the above range, the diameter of the carbon nanotube structure can be appropriately controlled without destroying the carbon nanotube structure during the dispersion process, and a dispersion having a uniform composition can be prepared.
[0106] The rotation speed of the container may be in the range of 500RPM to 10,000RPM, for example, 2,000RPM to 6,000RPM. When the rotation speed satisfies the above range, the diameter of the carbon nanotube structure can be properly controlled without destroying the carbon nanotube structure during the dispersion process, and a dispersion having a uniform composition can be prepared.
[0107] The duration of bead milling may be in the range of 0.5 to 2 hours, particularly 0.5 to 1.5 hours, and more particularly 0.8 to 1 hour. When the time satisfies the above range, the diameter of the carbon nanotube structure can be appropriately controlled without destroying the carbon nanotube structure during the dispersion process, and a dispersion having a uniform composition can be prepared. The operation time of bead milling refers to the total time of using the bead mill, and therefore, for example, if bead milling is performed several times, the operation time refers to the total time required to perform the bead milling several times.
[0108] The above bead milling conditions are for dispersing the bundle-type single-walled carbon nanotubes to a suitable level, and specifically exclude the case where the bundle-type single-walled carbon nanotubes are completely dispersed into single-chain single-walled carbon nanotubes. That is, the above bead milling conditions are for forming a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bound together side by side in the conductive agent dispersion prepared by appropriately dispersing the bundle-type single-walled carbon nanotubes. This can only be achieved when the composition of the mixed solution and the conditions of the dispersion process (e.g., bead milling process) are strictly controlled.
[0109] The carbon nanotube structure dispersion can be formed by the above method.
[0110] If necessary, a binder may be further included in the negative electrode slurry (the first negative electrode slurry and the second negative electrode slurry). In this case, the binder of the above embodiment may be used as the binder. (2) Forming a first negative electrode active material layer on the negative electrode current collector using the first negative electrode slurry and forming a second negative electrode active material layer on the first negative electrode active material layer using the second negative electrode slurry
[0111] Next, a first negative electrode active material layer is formed by using the first negative electrode slurry prepared as described above. Specifically, the first negative electrode active material layer can be prepared by coating the first negative electrode slurry on the negative electrode collector and drying the coated negative electrode collector, or the first negative electrode slurry can be cast on a separate support and then the film separated from the support is laminated on the negative electrode collector to prepare the first negative electrode active material layer. If necessary, the first negative electrode active material layer is formed by the above method, and then a rolling process can be further performed. In this case, considering the physical properties of the negative electrode to be finally prepared, drying and rolling can be performed under appropriate conditions, and there is no particular restriction.
[0112] Thereafter, a second negative electrode active material layer is formed by using the second negative electrode slurry prepared as described above. Specifically, the second negative electrode active material layer can be prepared by coating the second negative electrode slurry on the first negative electrode active material layer and drying the second negative electrode slurry, or the second negative electrode active material layer can be prepared by casting the second negative electrode slurry on a separate support and then laminating the thin film separated from the support on the first negative electrode active material layer. If necessary, the second negative electrode active material layer is formed by the above method, and then a rolling process can be further performed. In this case, taking into account the physical properties of the negative electrode to be finally prepared, drying and rolling can be performed under appropriate conditions, and there is no particular restriction.
[0113] Secondary battery
[0114] Next, a secondary battery according to another embodiment of the present invention will be described.
[0115] A secondary battery according to another embodiment of the present invention may include the negative electrode of the above embodiment.
[0116] Specifically, the secondary battery may include the negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode is the same as the negative electrode of the above embodiment. Since the negative electrode has been described above, its detailed description will be omitted.
[0117] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including a positive electrode active material.
[0118] In the positive electrode, there is no particular restriction on the positive electrode collector, as long as it has conductivity without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, or silver can be used. In addition, the positive electrode collector can generally have a thickness of 3 μm to 500 μm, and can have a surface with a fine roughness to improve adhesion to the positive electrode active material. The positive electrode collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.
[0119] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may include: a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound substituted by one or more transition metals; a lithium iron oxide such as LiFe3O4; a lithium manganese oxide such as Li 1+c1 Mn 2-c1O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, and Cu2V2O7; LiNi 1-c2 M c2 Ni-type lithium nickel oxide represented by O2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and c2 satisfies 0.01≤c2≤0.3); 2-c3 M c3 O2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and c3 satisfies 0.01≤c3≤0.1) or a lithium manganese composite oxide represented by the chemical formula Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4 having a portion of Li substituted by alkaline earth metal ions; but the positive electrode active material is not limited thereto. The positive electrode may be lithium metal.
[0120] The positive electrode active material layer may include a positive electrode conductor and a positive electrode binder as well as the positive electrode active material described above.
[0121] In this case, the positive electrode conductive agent is used to provide conductivity to the electrode, wherein any conductive agent can be used without particular limitation as long as it has electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of the positive electrode conductive agent may be graphite, such as natural graphite and artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders, such as copper powder, nickel powder, aluminum powder, and silver powder, or metal fibers; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as derivatives of polyphenylene, one of which may be used alone or a mixture of two or more thereof.
[0122] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples of the positive electrode binder can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, one of which can be used alone or a mixture of two or more thereof can be used.
[0123] The separator separates the negative electrode and the positive electrode and provides a mobile path for lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is a separator commonly used in a secondary battery, in particular, a separator having high moisture retention capacity for electrolytes and low resistance to the transfer of electrolyte ions can be used. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure with more than two layers can be used. In addition, a typical porous nonwoven fabric can be used, such as a nonwoven fabric formed by a high melting point glass fiber or a polyethylene terephthalate fiber. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator with a single-layer structure or a multilayer structure can be selectively used.
[0124] The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that can be used in the preparation of a lithium secondary battery, but the present invention is not limited thereto.
[0125] Specifically, the electrolyte may include a nonaqueous organic solvent and a lithium salt.
[0126] Examples of the nonaqueous organic solvent may be aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0127] Especially, ethylene carbonate and propylene carbonate are cyclic carbonates in carbonate-based organic solvents, and cyclic carbonates as high-viscosity organic solvents dissociate lithium salts well in electrolytes due to high dielectric constant, and therefore cyclic carbonates can be preferably used. Since when cyclic carbonates are mixed with low-viscosity, low-dielectric-constant straight-chain carbonates such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, an electrolyte with high conductivity can be prepared, therefore cyclic carbonates are more preferably used.
[0128] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily soluble in a non-aqueous electrolyte. For example, a lithium salt selected from the group consisting of F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - , and (CF3CF2SO2)2N - Any one of the constituted groups serves as an anion of the lithium salt.
[0129] For the purpose of improving the life characteristics of the battery, preventing the reduction of the battery capacity, and increasing the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, at least one additive may be further included in the electrolyte, for example, a halogenated alkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum chloride.
[0130] According to another embodiment of the present invention, a battery module including the secondary battery as a unit cell and a battery pack including the battery module are provided. The battery module and the battery pack include secondary batteries having high capacity, high rate characteristics, and high cycle characteristics, and the battery module and the battery pack can be used as power sources for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0131] Hereinafter, the present invention will be described in more detail according to specific embodiments.
[0132] Preparation Example 1: Preparation of Carbon Black Dispersion
[0133] 0.4 parts by weight of carbon black (Imerys Graphite & Carbon, Super C65) having an average particle size of 35 nm and 0.6 parts by weight of carboxymethyl cellulose (weight average molecular weight: 100,000 g / mol, degree of substitution: 1.0) were mixed in 99.0 parts by weight of water as a dispersion medium to prepare a mixed solution so that the solid content was 1.0 weight %. The mixed solution was stirred by a beads-mill method to disperse the carbon black in a solvent, and a carbon black dispersion was thus prepared. In this case, the diameter of the beads was 1 mm, and the rotation speed of the container containing the beads was 3,000 RPM for 60 minutes.
[0134] In the carbon black dispersion, the amount of carbon black was 0.4% by weight, and the amount of carboxymethyl cellulose was 0.6% by weight.
[0135] Preparation Example 2: Preparation of Carbon Nanotube Structure Dispersion
[0136] 0.4 parts by weight of bundled carbon nanotubes (specific surface area of 650 m 2 / g) and 0.6 parts by weight of carboxymethyl cellulose (weight average molecular weight: 100,000 g / mol, degree of substitution: 1.0) were mixed in 99.0 parts by weight of water as a dispersion medium to prepare a mixture so that the solid content was 1.0% by weight.
[0137] The mixture was stirred by a beads-mill method to disperse the bundle-type single-walled carbon nanotubes in a solvent, and a carbon nanotube structure dispersion was prepared thereby. In this case, the diameter of the beads was 1 mm, the rotation speed of the container containing the beads was 3,000 RPM, and stirring was performed for 60 minutes. The carbon nanotube structure dispersion includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined side by side.
[0138] In the carbon nanotube structure dispersion, the amount of the carbon nanotube structure was 0.4% by weight, and the amount of the carboxymethyl cellulose was 0.6% by weight.
[0139] Preparation Example 3: Preparation of Carbon Nanotube Structure Dispersion
[0140] A carbon nanotube structure dispersion was prepared in the same manner as in Preparation Example 2, except that the weight average molecular weight of the carboxymethyl cellulose in Preparation Example 2 was changed to 400,000 g / mol (degree of substitution: 1.0). In this dispersion, the amount of the carbon nanotube structure was 0.4 wt % and the amount of the carboxymethyl cellulose was 0.6 wt %.
[0141] Preparation Example 4: Preparation of single-walled carbon nanotube unit dispersion
[0142] 0.2 parts by weight of bundled carbon nanotubes (specific surface area of 650 m 2 / g) and 1.2 parts by weight of carboxymethyl cellulose (weight average molecular weight: 100,000 g / mol, degree of substitution: 1.0) were mixed in 98.6 parts by weight of water as a dispersion medium to prepare a mixture so that the solid content was 1.4% by weight.
[0143] The mixture is stirred by a beads-mill method, and the bundle-type single-walled carbon nanotubes are dispersed in a solvent, and a single-walled carbon nanotube unit dispersion is prepared thereby. In this case, the diameter of the beads is 1 mm, and the rotation speed of the stirring container containing the beads is 3,000 RPM. Stirring for 60 minutes under this condition is set as 1 cycle, and a total of 4 cycles are performed (natural cooling for 60 minutes between each cycle). Therefore, a single-walled carbon nanotube unit dispersion is prepared. In this dispersion, since the bundle-type single-walled carbon nanotubes are completely dispersed, the single-walled carbon nanotube unit exists only as a single-chain unit, but the above-mentioned carbon nanotube structure is not detected. In addition, in the single-walled carbon nanotube unit dispersion, the amount of the single-walled carbon nanotube unit is 0.2% by weight, and the amount of the carboxymethyl cellulose is 1.2% by weight.
[0144] Preparation Example 5: Preparation of Multi-walled Carbon Nanotube Unit Dispersion
[0145] 4.0 parts by weight of bundled carbon nanotubes (specific surface area 185 m 2 / g) and 0.6 parts by weight of carboxymethyl cellulose (weight average molecular weight: 100,000 g / mol, degree of substitution: 1.0) were mixed in 95.4 parts by weight of water as a dispersion medium to prepare a mixed liquid so that the solid content was 4.6% by weight.
[0146] The mixed solution was added to a pin crusher filled with 80% beads having a size of 0.65 mm, dispersed, and discharged at a discharge rate of 2 kg / min. The bundle-type multi-walled carbon nanotubes were completely dispersed by performing this process twice to prepare a multi-walled carbon nanotube unit dispersion. In the dispersion, the amount of multi-walled carbon nanotube units (average diameter: 10 nm) was 4.0% by weight, and the amount of carboxymethyl cellulose was 0.6% by weight.
[0147] Examples and Comparative Examples
[0148] Example 1: Preparation of negative electrode
[0149] (1) Forming the first negative electrode active material layer
[0150] The carbon black dispersion of Preparation Example 1, the average particle size (D 50 ) is 21 μm in thickness, and styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) (weight average molecular weight: 100,000 g / mol, degree of substitution: 1.0) as a binder are mixed with water to prepare a first negative electrode slurry. The negative electrode slurry is coated on a 20 μm thick negative electrode collector (copper (Cu) film), dried at 130° C., and then rolled to form a first negative electrode active material layer (thickness: 50 μm).
[0151] 94.80 wt % of artificial graphite, 3.5 wt % of SBR, 1.2 wt % of CMC, and 0.50 wt % of carbon black were included in the first negative active material layer.
[0152] (2) Forming the Second Negative Electrode Active Material Layer
[0153] The carbon nanotube structure dispersion of Preparation Example 2 and the negative electrode active material (average particle size (D 50 ) is 21 μm for artificial graphite: average particle size (D 50 ) with a weight ratio of SiO of 6.6 μm = 94:6), SBR and carboxymethyl cellulose (CMC) (weight average molecular weight: 100,000 g / mol, degree of substitution: 1.0) as a binder were mixed with water to prepare a second negative electrode slurry. The second negative electrode slurry was coated on the first negative electrode active material layer, dried at 130°C, and then rolled to form a second negative electrode active material layer (thickness: 50 μm)
[0154] The second negative electrode active material layer included 96.25 wt % of negative electrode active material, 2.5 wt % of SBR, 1.2 wt % of CMC, and 0.05 wt % of carbon nanotube structure in total.
[0155] Example 2: Preparation of negative electrode
[0156] A negative electrode was prepared in the same manner as in Example 1, except that the carbon nanotube structure dispersion of Preparation Example 3 was used instead of the carbon nanotube structure dispersion of Preparation Example 2 when forming the second negative electrode active material layer of Example 1.
[0157] Example 3: Preparation of negative electrode
[0158] A negative electrode was prepared in the same manner as in Example 1, except that during the formation of the first negative electrode slurry of Example 1, the multi-walled carbon nanotube unit dispersion of Preparation Example 5 was used instead of the carbon black dispersion of Preparation Example 1.
[0159] Example 4: Preparation of negative electrode
[0160] The negative electrode was prepared in the same manner as in Example 1, except that during the formation of the first negative electrode slurry of Example 1, the carbon nanotube structure dispersion of Preparation Example 2 and the multi-walled carbon nanotube unit dispersion of Preparation Example 5 were used instead of the carbon black dispersion of Preparation Example 1. The weight ratio of the carbon nanotube structure to the multi-walled carbon nanotube in the prepared first negative electrode active material layer was 10:90. The first negative electrode active material layer included 94.80 wt% of artificial graphite, 3.5 wt% of SBR, 1.2 wt% of CMC, 0.05 wt% of the carbon nanotube structure, and 0.45 wt% of the multi-walled carbon nanotube unit.
[0161] Example 5: Preparation of negative electrode
[0162] A negative electrode was prepared in the same manner as in Example 1, except that during the formation of the first negative electrode slurry of Example 1, the carbon nanotube structure dispersion of Preparation Example 2 was used instead of the carbon black dispersion of Preparation Example 1.
[0163] 95.25 wt % of artificial graphite, 3.5 wt % of SBR, 1.2 wt % of CMC, and 0.05 wt % of carbon nanotube structure were included in the first negative active material layer.
[0164] Comparative Example 1: Preparation of negative electrode
[0165] The carbon nanotube structure dispersion of Preparation Example 2 and the negative electrode active material (average particle size (D 50 ) is 21 μm for artificial graphite: average particle size (D 50 ) with a weight ratio of SiO of 6.6 μm = 94:6), SBR and carboxymethyl cellulose (CMC) (weight average molecular weight: 100,000 g / mol, degree of substitution: 1.0) as a binder were mixed with water to prepare a negative electrode slurry. The negative electrode slurry was coated on a 20 μm thick negative electrode collector (copper (Cu) film), dried at 130° C., and then roll-pressed to form a negative electrode active material layer (thickness: 100 μm).
[0166] The negative electrode active material layer included 95.75 wt % of the negative electrode active material, 3.0 wt % of the SBR, 1.2 wt % of the CMC, and 0.05 wt % of the carbon nanotube structure in total.
[0167] Comparative Example 2: Preparation of negative electrode
[0168] A negative electrode was prepared in the same manner as in Example 1, except that during the formation of the second negative active material layer of Example 1, the single-walled carbon nanotube unit dispersion of Preparation Example 4 was used instead of the carbon nanotube structure dispersion of Preparation Example 2.
[0169] The second negative electrode active material layer includes a total of 96.25 wt % of negative electrode active material (average particle size (D 50 ) is 21 μm for artificial graphite: average particle size (D 50 ) with a weight ratio of SiO of 6.6 μm = 94:6), 2.5 wt% SBR, 1.2 wt% CMC, and 0.05 wt% single-walled carbon nanotube units.
[0170] Comparative Example 3: Preparation of negative electrode
[0171] A negative electrode was prepared in the same manner as in Example 1, except that during the formation of the second negative active material layer of Example 1, the multi-walled carbon nanotube unit dispersion of Preparation Example 5 was used instead of the carbon nanotube structure dispersion of Preparation Example 2.
[0172] The second negative electrode active material layer includes a total of 95.80 wt % of negative electrode active materials (average particle size (D 50 ) is 21 μm for artificial graphite: average particle size (D 50 ) with a weight ratio of SiO of 6.6 μm = 94:6), 2.5 wt% SBR, 1.2 wt% CMC, and 0.5 wt% multi-walled carbon nanotube units.
[0173] [Table 1]
[0174]
[0175] In Examples 1, 3 to 5 and Comparative Example 1, the average diameter of the carbon nanotube structure was 10 nm and the average length was 8.2 μm. In Example 2, the average diameter of the carbon nanotube structure was 100 nm and the average length was 15.6 μm. In Comparative Example 2, the average diameter of the single-walled carbon nanotube unit was 1.6 nm and the average length was 1.8 μm.
[0176] In the negative electrodes of Examples 3, 4 and Comparative Example 3, the average diameter of the multi-walled carbon nanotube units was 10.8 nm, and the average length was 1.3 μm.
[0177] When the prepared negative electrode is observed by a transmission electron microscope (TEM), the average diameter and the average length correspond to the average value of the diameters (or lengths) of the first 100 carbon nanotube structures (or multi-walled carbon nanotube units, or single-walled carbon nanotube units) and the last 100 carbon nanotube structures (or multi-walled carbon nanotube units, or single-walled carbon nanotube units) having a large diameter (or length).
[0178] Test Example 1: Observation of the negative electrode
[0179] (1) Adhesive distribution
[0180] Figure 1It is an analysis diagram of the binder distribution in the negative electrode of Comparative Example 1 and the negative electrode of Example 1. It was analyzed by osmium oxide (OsO4) staining. Specifically, the negative electrode was stained by exposing / standing for 3 days in an atmosphere of osmium oxide smoke in a sealed special chamber prepared in a glove box, and the atmosphere was replaced with an argon (Ar) atmosphere. One day later, the cross section of the negative electrode cut by ion milling was analyzed by image mapping using scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX).
[0181] Figure 1 The influence of the analysis of Comparative Example 1 (left) in which the negative electrode active material layer is formed as a single layer and Example 1 (right) in which the first and second negative electrode active material layers are formed. Referring to the right figure, it can be understood that in Example 1, the first negative electrode active material layer and the second negative electrode active material layer have different compositions from each other, and it can be understood that the binder distribution ratios of the first negative electrode active material layer and the second negative electrode active material layer are also different from each other. In particular, in the case where the first negative electrode active material layer and the second negative electrode active material layer are formed separately as in Example 1, it can be understood that SiO is only located in the second negative electrode active material layer, and it can be understood that the content of the binder in the first negative electrode active material layer is large. In addition, it can be understood that the binder distribution changes along the thickness direction of the negative electrode active material layer.
[0182] (2) Confirmation of the existence of carbon nanotube structure
[0183] Figure 2 is a SEM image of the second negative electrode active material layer of the negative electrode of Example 1, Figure 3 3 is a SEM image of the second negative electrode active material layer of the negative electrode of Example 2. Figure 4 3 is a SEM image of the second negative electrode active material layer of the negative electrode of Comparative Example 3. Figure 6 3 is a SEM image of the second negative electrode active material layer of the negative electrode of Comparative Example 2.
[0184] Reference Figure 2 and Figure 3 , it can be confirmed that there is a carbon nanotube structure in the form of a long rope, in which multiple single-walled carbon nanotube units are arranged side by side and bonded to each other. In particular, it can be understood that Figure 2 In the negative electrode of Example 1, since hydrogenated nitrile rubber having a relatively low weight average molecular weight is used, a carbon nanotube structure having an average diameter of about 10 nm is formed, and Figure 3 It is understood that a carbon nanotube structure with an average diameter of about 100 nm is formed. Figure 2 and Figure 3In the process, carbon nanotube structures form a network structure with each other.
[0185] In contrast, Figure 4 Only short-length multi-walled carbon nanotube units were shown, but no carbon nanotube structure was observed. Figure 6 In the figure, only the single-walled carbon nanotube units present in the single chain units are shown, but the carbon nanotube structure is not observed.
[0186] (3) Confirm the network of the second conductive agent
[0187] Figure 5 This is a SEM image of the second negative electrode active material layer of the negative electrode of Example 1. Figure 5 (A), it can be understood that cracks in SiO can be suppressed by the carbon nanotube structure. Figure 5 (B), it can be understood that the carbon nanotube structure is maintained on the broken SiO, so that the conductive network is not destroyed. Figure 5 As can be understood from (C), due to the longer length of the carbon nanotube structure, a longer conductive network is formed.
[0188] Test Example 2: Evaluation of negative electrode adhesion
[0189] The negative electrode adhesion (adhesion between the negative electrode active material layer and the current collector) was measured under dry conditions. Specifically, a double-sided tape was attached to a glass slide, and each negative electrode punched out to a size of 20 mm × 180 mm was placed thereon, and a 2 kg roller was reciprocated 10 times to attach the electrode to the tape, and then a universal testing machine (UTM, TA Instruments) was used to pull the electrode at a speed of 200 mm / min to measure the force of separation from the glass slide. In this case, the measurement angle between the glass slide and the negative electrode was 90 °. The measurement results are listed in Table 2 below.
[0190] Test Example 3: Evaluation of Adhesion Between the First Negative Electrode Active Material Layer and the Second Negative Electrode Active Material Layer
[0191] The shear strengths (N / mm) of Examples 1 to 4 and Comparative Examples 1 to 3 were measured by the following method: 2 ). The measurement was performed using SAICAS (Surface and Interfacial Characterization Analysis System) (SAICAS EN-EX, Daipla Wintes Japan). Specifically, when each negative electrode was beveled from its surface to its interior using a diamond microblade, the shear strength was measured from the force applied to the interface between the first negative electrode active material layer and the second negative electrode active material layer, and the results are listed in Table 2 below.
[0192] Test Example 4: Evaluation of Capacity Retention and Discharge Capacity Based on C-Rate
[0193] Batteries were prepared using the negative electrodes of Examples 1 to 5 and Comparative Examples 1 to 3, respectively, as follows.
[0194] Using Li[Ni 0.6 Mn 0.2 Co 0.2 ]O2 was used as a positive electrode active material. The positive electrode active material, carbon black as a conductive agent, and polyvinylidene fluoride (PVdF) as a binder were mixed in a weight ratio of 94:4:2 in an N-methyl-2-pyrrolidone solvent to prepare a positive electrode slurry.
[0195] The prepared positive electrode slurry was coated on a 15 μm thick aluminum metal film as a positive electrode collector and dried. In this case, the temperature of the circulating air was 110° C. Subsequently, the coated and dried positive electrode collector was roll-pressed and dried in a vacuum oven at 130° C. for 2 hours to form a positive electrode active material layer.
[0196] Each negative electrode of Examples 1 to 5 and Comparative Examples 1 to 3, the positive electrode prepared above, and a porous polyethylene separator are assembled by using a stacking method, and an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 1 / 2 (volume ratio), lithium hexafluorophosphate (LiPF6 1 mol)) is injected into the assembled battery to prepare a lithium secondary battery.
[0197] 1) Evaluate discharge capacity based on C-Rate
[0198] The charge C-Rate was fixed at 0.2C, and the 2.0C discharge capacity (%) of each lithium secondary battery relative to the 0.2C discharge capacity was measured while increasing the discharge C-Rate from 0.2C to 2.0C, and the results are listed in Table 2.
[0199] 2) Evaluation of capacity retention (lifespan characteristics)
[0200] Charging and discharging of each lithium secondary battery were performed under the following conditions.
[0201] Each lithium secondary battery was charged and discharged at 0.33C / 0.33C in the voltage range of 4.25V to 2.8V at 45°C as one cycle, and a total of 100 cycles were performed. Thereafter, the discharge capacity (capacity retention rate) after 100 cycles was evaluated based on the 100% discharge capacity after one cycle, and is listed in Table 2.
[0202] [Table 2]
[0203]
[0204] Referring to Table 2, when the second negative electrode active material layer includes a carbon nanotube structure, it can be understood that the input / output characteristics and life characteristics of the battery can be improved, and the negative electrode adhesion and the adhesion between the first negative electrode active material layer and the second negative electrode active material layer can be improved.
[0205] The present application further includes the following embodiments:
[0206] 1. A negative electrode, comprising a negative electrode current collector, a first negative electrode active material layer disposed on the negative electrode current collector, and a second negative electrode active material layer disposed on the first negative electrode active material layer,
[0207] wherein the second negative electrode active material layer comprises a second negative electrode active material and a second conductive agent,
[0208] wherein the second negative electrode active material comprises a silicon-based active material,
[0209] The silicon-based active material includes SiO x (0≤x<2),
[0210] The second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bound side by side, and
[0211] The carbon nanotube structure is included in the second negative active material layer in an amount of 0.01 wt % to 1.0 wt %.
[0212] Embodiment 2. The negative electrode as described in Embodiment 1, wherein the carbon nanotube structures are interconnected in the second negative electrode active material layer to form a network structure.
[0213] Embodiment 3. The negative electrode according to Embodiment 1, wherein, in the carbon nanotube structure, the single-walled carbon nanotube units are combined in a state where long axes of the single-walled carbon nanotube units are arranged parallel to each other.
[0214] Embodiment 4. The negative electrode as described in Embodiment 1, wherein the average length of the carbon nanotube structure is 1 μm to 500 μm.
[0215] Embodiment 5. The negative electrode as described in Embodiment 1, wherein the average length of the carbon nanotube structure is 2 μm to 50 μm.
[0216] Embodiment 6. The negative electrode as described in Embodiment 1, wherein the average diameter of the carbon nanotube structure is 2 nm to 500 nm.
[0217] Embodiment 7. The negative electrode as described in Embodiment 1, wherein the average diameter of the carbon nanotube structure is 5 nm to 200 nm.
[0218] Embodiment 8. The negative electrode as described in Embodiment 1, wherein, in the carbon nanotube structure, the average diameter of the single-walled carbon nanotube unit is 0.5 nm to 10 nm.
[0219] Embodiment 9. The negative electrode as described in Embodiment 1, wherein the carbon nanotube structure is a carbon nanotube structure in which 2 to 50 single-walled carbon nanotube units are bonded to each other.
[0220] Embodiment 10. The negative electrode as described in Embodiment 1, wherein the first negative electrode active material layer includes a first negative electrode active material and a first conductive agent, and
[0221] The first conductive agent includes at least one selected from the group consisting of the carbon nanotube structure, a multi-walled carbon nanotube unit, graphene, and carbon black.
[0222] Embodiment 11. The negative electrode as described in Embodiment 1, wherein the thickness of the first negative electrode active material layer is 1 μm to 100 μm.
[0223] Embodiment 12. The negative electrode as described in Embodiment 1, wherein the thickness of the second negative electrode active material layer is 1 μm to 100 μm.
[0224] Embodiment 13. A secondary battery comprising the negative electrode described in Embodiment 1.
Claims
1. A negative electrode, comprising a negative electrode current collector, a first negative electrode active material layer disposed on the negative electrode current collector, and a second negative electrode active material layer disposed on the first negative electrode active material layer, wherein the first negative electrode active material layer comprises a first negative electrode active material and a first conductive agent, and the first conductive agent comprises at least one selected from the group consisting of a carbon nanotube structure and a multi-walled carbon nanotube unit, wherein the second negative electrode active material layer comprises a second negative electrode active material and a second conductive agent, wherein the second negative electrode active material comprises a silicon-based active material, The silicon-based active material includes SiO x (0≤x<2), and The second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded side by side. 2 . The negative electrode of claim 1 , wherein the carbon nanotube structures are interconnected in the second negative electrode active material layer to form a network structure.
3. The negative electrode according to claim 1, wherein In the carbon nanotube structure, the single-walled carbon nanotube units are combined in a state where long axes of the single-walled carbon nanotube units are arranged parallel to each other. 4 . The negative electrode according to claim 1 , wherein the average length of the carbon nanotube structure is 1 μm to 500 μm. 5 . The negative electrode according to claim 1 , wherein the average length of the carbon nanotube structure is 2 μm to 50 μm. The negative electrode according to claim 1 , wherein the average diameter of the carbon nanotube structure is 2 nm to 500 nm. 7 . The negative electrode as claimed in claim 1 , wherein the average diameter of the carbon nanotube structure is 5 nm to 200 nm.
8. The negative electrode according to claim 1, wherein In the carbon nanotube structure, the average diameter of the single-walled carbon nanotube unit is 0.5 nm to 10 nm. 9 . The negative electrode of claim 1 , wherein the carbon nanotube structure is a carbon nanotube structure in which 2 to 50 single-walled carbon nanotube units are bonded to each other. 10 . The negative electrode of claim 1 , wherein the first negative electrode active material layer has a thickness of 1 μm to 100 μm. 11 . The negative electrode of claim 1 , wherein the second negative electrode active material layer has a thickness of 1 μm to 100 μm. 12 . A secondary battery comprising the negative electrode according to claim 1 .
